Development and evaluation of natural gum-based extended release matrix tablets of two model drugs of different water solubilities by direct compression - Kwabena Ofori-Kwakye; Kwadwo Amanor Mfoafo; Samuel Lugrie Kipo; Noble Kuntworbe; Mariam El Boakye-Gyasi (Elsevier, 2016)
The study was aimed at developing extended release matrix tablets of poorly water-soluble diclofenac sodium and highly water-soluble metformin hydrochloride by direct compression using cashew gum, xanthan gum and hydroxypropylmethylcellulose (HPMC) as release retardants. The suitability of light grade cashew gum as a direct compression excipient was studied using the SeDeM Diagram Expert System. Thirteen tablet formulations of diclofenac sodium (∼100 mg) and metformin hydrochloride (∼200 mg) were prepared with varying amounts of cashew gum, xanthan gum and HPMC by direct compression. The flow properties of blended powders and the uniformity of weight, crushing strength, friability, swelling index and drug content of compressed tablets were determined. In vitro drug release studies of the matrix tablets were conducted in phosphate buffer (diclofenac: pH 7.4; metformin: pH 6.8) and the kinetics of drug release was determined by fitting the release data to five kinetic models. Cashew gum was found to be suitable for direct compression, having a good compressibility index (ICG) value of 5.173. The diclofenac and metformin matrix tablets produced generally possessed fairly good physical properties. Tablet swelling and drug release in aqueous medium were dependent on the type and amount of release retarding polymer and the solubility of drug used. Extended release of diclofenac (∼24 h) and metformin (∼8-12 h) from the matrix tablets in aqueous medium was achieved using various blends of the polymers. Drug release from diclofenac tablets fitted zero order, first order or Higuchi model while release from metformin tablets followed Higuchi or Hixson-Crowell model. The mechanism of release of the two drugs was mostly through Fickian diffusion and anomalous non-Fickian diffusion. The study has demonstrated the potential of blended hydrophilic polymers in the design and optimization of extended release matrix tablets for soluble and poorly soluble drugs by direct compression. Keywords: Cashew gum, Xanthan gum, HPMC, Direct compression, SeDeM Diagram Expert System, Diclofenac sodium, Metformin hydrochloride